DISPARITY BETWEEN CRIMINAL SANCTIONS IN THE KUHP AND LAW NUMBER 1 OF 2023 CONCERNING THE CRIMINAL CODE - Halilintar, Ilham Saputra; Nasihuddin, Abdul Aziz (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Criminal Code (KUHP) is a legacy of the Dutch colonial era. Its substance and principles are still influenced by individualistic and colonialist views that are not in line with the ideological values of the Indonesian nation. With the enactment of Law Number 1 of 2023 concerning the Criminal Code, Indonesia seeks to reform its criminal law system to be more in line with social, cultural values, and current and future societal conditions. This study aims to analyze the differences or disparities in criminal sanctions between the old Criminal Code and Law Number 1 of 2023 concerning the Criminal Code. The method used is normative legal research, namely by examining the provisions of sanctions in both regulations in depth and systematically. The results of the study indicate that criminal sanctions and actions in the National Criminal Code for their imposition on perpetrators must pay attention to the provisions of 1) the purpose of punishment (Article 51-Article 52); 2) guidelines for punishment (Article 53-Article 56); 3) guidelines for the application of imprisonment with a single formulation and alternative formulation (Article 57); 4) aggravation of the sentence (Article 58-Article 59); 5) other provisions regarding sentencing (Article 60-Article 63). This is quite different from the use of types of criminal sanctions in the Criminal Code, which does not recognize these five important things to pay attention to because they are not regulated in the Criminal Code. The purpose of sentencing is one important aspect that forms the basis for analyzing the provisions of the main criminal sanctions in both regulations.